Tuturan Tradisi Lisan Mandi Tolak Bala Suku Bajau Pulau Balikukup Kecamatan Batu Putih Kabupaten Berau Ditinjau Dari Puisi Lama - Setyawati, Meita; Suwilta, Waode (Adjektiva: Educational Languages and Literature Studies, 2022)
This study aim to describe the form of the oral tradition of bathing rejects reinforcements from the Bajau tribe, Batu Putih District, Berau Regency in terms of old poetry. the oral tradition of bathing rejects reinforcements from the Bajau tribe, Batu Putih District, Berau Regency in terms of old poetry. This type of research is qualitative using descriptive method. Data collection techniques used are observation techniques, reading and note-taking techniques, and interview techniques. The steps used are as follows as data analysis in this study, namely collecting data to be analyzed relating to the bathing reject bala tradition, reducing relevant data, analyzing the tradition, namely describing the oral tradition of bathing tolak bala, describing the process of the oral tradition of bathing tolak bala, describe the meaning of the oral tradition of bathing reject reinforcements of the Bajau tribe, Batu Putih District, Berau Regency. From the results of the study, it was found that the form of oral tradition speech was in the form of an old poem with n-n-n-n rhymes, namely poetry, the process and meaning of taking a bath for the Bajau tribe, including making calls using musical instruments, namely gongs, separating men and women, here the first session for women (after all the series is carried out followed by men with the same process).